Pengendalian Kualitas Produksi Crude Palm Oil PKS Sawit Seberang PT. Perkebunan Nusantara II - Yusmani Buulolo (JEMA: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
The development of the palm oil processing industry has given rise to highly competitive competition between companies, especially the palm oil mill industry in North Sumatra. Padang Tualang Palm Oil Mill (PKS) Sawit Seberang unit is one of the palm oil industries that produces crude palm oil or called Crude Palm Oil (CPO). This study aims to control the quality of CPO production at PT. Perkebunan Nusantara II. CPO quality control at PKS Sawit Seberang PTPN-II is carried out because there is CPO quality data that is still outside the standard limits. Quality control is carried out using the statistical quality control method, namely quality control using a statistical approach using 2 quality control tools, namely the X and R control charts and cause and effect diagrams. From this study, it was found that there were 6 data that were outside the control limits for free fat acid levels and 7 data for water content. The impurity content did not experience any change because the same value was 0.018. In the cause and effect diagram, it was found that several factors that affect CPO quality were; materials, machines, humans, and methods. Therefore, to improve CPO quality, companies must pay closer attention to these factors.